Effect of Self- Efficacy Promoting Program on Self- Efficacy and Safety Behavior of Caretaker among Pre-School Children in Low Income and Multiple Deprived Families - กล่อมเมฆ, จิราวรรณ; ตีวารี, ชญาภรณ์; ผลิตผลการพิมพ์, อดิศักดิ์ (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental one-group pretest – posttest research aimed to compare self-efficacy and safety behavior of caretaker among pre-school children in low income and multiple deprived families study before and after of self- efficacy promoting program. Simple random sampling with inclusion criteria was used to recruit a sample of 30 caretakers who are living in Bangkok. The instruments used in this research include a demographic questionnaire, self- efficacy of the caretaker questionnaire, and safety behavior of the caretaker questionnaire. All instruments had content validity. The Cronbach’s alpha reliability of the questionnaires was .90 and .86 respectively. Data were analyzed by using descriptive statistic and t-test with statistical significance at .05. The results found after the program showed that mean score of self- efficacy and safety behavior of caretaker among pre-school children were higher than before the program with a statistic significant (t30 = 5.23, p < .001 and t30 = 5.23, p < .001 respectively). These findings suggest that nurses and other health policymakers relating to child safety could apply this self- efficacy promoting program to build up policies protecting home child’s injuries in low income and multiple deprived families.